ANALISIS MODAL KERJA DAN PROFITABILITAS PADA PT. WAHANA SUMBER LESTARI SAMARINDA DI SAMARINDA - -, amad Munaji (EKONOMIA, 2014)
This study aimed to calculate and test the amount of working capital and profitability on PT. Wahana Sumber Lestari Samarinda. The problem in this study is “